1986
DOI: 10.1002/ana.410190120
|View full text |Cite
|
Sign up to set email alerts
|

Neurological involvement in hemolytic‐uremic syndrome

Abstract: Of 44 children with hemolytic-uremic syndrome seen at Milwaukee Children's Hospital, 15 (34%) had neurological involvement. This group contained 8 boys and 7 girls, with a mean age of 3 1/4 years. Twelve patients had seizure within 48 hours of admission. Seizures were associated with hypertension, fever, hyponatremia, or hypocalcemia. Other neurological symptoms included altered consciousness, behavioral changes, diplopia, and dizziness. Hemiparesis (4 patients), eye involvement (7 patients), decerebrate postu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
0
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(71 citation statements)
references
References 10 publications
5
65
0
1
Order By: Relevance
“…Neurologic evaluation and follow-up of patients with CNS symptoms allowed early detection of subtle vision dysfunction, visual perception deficit, and mild cognitive disabilities. Incidence of neurologic symptoms in acute phase of HUS in this group (39%) was similar to former descriptive studies (Sheth et al, 1986;Hahn et al, 1989;Garel et al, 2004;Steinborn et al, 2004); orolingual dystonia was previously observed, but cortical blindness, hallucinations (Cimolai et al, 1896) and cerebellar mutism/anarthria (Mewasingh et al, 2003) were not observed in our group. A slightly higher prevalence in girls was identified (boy/girl rate 1:1.2), as reported by other authors (Cimolai et al, 1986;Rivero et al, 2004;Zambrano et al, 2005); this rate is increased to 1:1,7 when regarding the neurologic patients, perhaps related to specific auto-immune characteristics.…”
Section: Commentssupporting
confidence: 92%
“…Neurologic evaluation and follow-up of patients with CNS symptoms allowed early detection of subtle vision dysfunction, visual perception deficit, and mild cognitive disabilities. Incidence of neurologic symptoms in acute phase of HUS in this group (39%) was similar to former descriptive studies (Sheth et al, 1986;Hahn et al, 1989;Garel et al, 2004;Steinborn et al, 2004); orolingual dystonia was previously observed, but cortical blindness, hallucinations (Cimolai et al, 1896) and cerebellar mutism/anarthria (Mewasingh et al, 2003) were not observed in our group. A slightly higher prevalence in girls was identified (boy/girl rate 1:1.2), as reported by other authors (Cimolai et al, 1986;Rivero et al, 2004;Zambrano et al, 2005); this rate is increased to 1:1,7 when regarding the neurologic patients, perhaps related to specific auto-immune characteristics.…”
Section: Commentssupporting
confidence: 92%
“…A search for DϩHUS with neurologic involvement in the literature resulted in retrieval of seven series that totaled approximately 150 patients (5)(6)(7)(8)(9)(10)(11). The French national survey of DϩHUS numbered 1308 cases between 1993 and 2007, and our patients, who were recruited from the same centers that participate to the French survey, include 39 cases in the same period, suggesting that the frequency of neurologic involvement is approximately 3%.…”
Section: Discussionmentioning
confidence: 95%
“…Stx binds to Gb3 receptors in neurons of the central nervous system of mice (26) and has been found to produce brain damage in mice (25). Neurological damage in humans is a frequent complication in HUS (32,51,61) and in experimental animals (rabbits) exposed to Stx (14,56). We reasoned that administration of a lower dose of Stx2 may allow the mice to survive for a longer period of time, permitting them to develop a symptomatic course that would more completely reproduce the characteristics of HUS.…”
Section: Discussionmentioning
confidence: 99%